Streptococcus Viridans meningitis in an immunocompetent child: A case report - Ali Goudarzi; Roham Sarmadian; Parsa Yousefichaijan; Abolfazl Gilani (Clinical Case Reports)
Abstract In bacterial meningitis, the Viridans streptococci group is not considered a prevalent pathogen. In contrast, the S. viridans group may cause endocarditis and fatal infections in immunocompromised children and adults. We report a 5‐year‐old immunocompetent boy with signs of meningitis. The CSF tested positive for meningitis with streptococcus viridans.